2010
DOI: 10.4314/wajae.v16i1.55865
|View full text |Cite
|
Sign up to set email alerts
|

Quality Protein Maize Response to Nitrogen Rate and Plant Density in the Guinea Savanna Zone of Ghana

Abstract: Field experiments were conducted in the Guinea savanna ecology of Ghana to evaluate yield response of quality protein maize (Zea mays L.) hybrid to plant density and nitrogen (N) fertilizer. The experiments were conducted at four locations on 16 farmers' fields in 2002 and 2003. Three N rates (0, 90 and 135 kg/ha) were combined with three plant densities (50 000, 62 500 and 71 400 plants/ha) to constitute nine treatments which were tested in a randomized complete block design. Optimal N rate was not affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
5
6
0
Order By: Relevance
“…Application of N from 40 kg N ha -1 to 120 kg N ha -1 had an increasing effect on grain yield. This finding agree with that of Buah et al, (2009) who reported that 120 kg N ha -1 currently produced the highest grain yield of maize in the Semi-Arid, Nigeria. Patel et al, (2006) and El-Gizawy, (2009) also supported the fact that increase in N application will always lead to increase in grain yield of maize.…”
Section: Discussionsupporting
confidence: 82%
“…Application of N from 40 kg N ha -1 to 120 kg N ha -1 had an increasing effect on grain yield. This finding agree with that of Buah et al, (2009) who reported that 120 kg N ha -1 currently produced the highest grain yield of maize in the Semi-Arid, Nigeria. Patel et al, (2006) and El-Gizawy, (2009) also supported the fact that increase in N application will always lead to increase in grain yield of maize.…”
Section: Discussionsupporting
confidence: 82%
“…Also, fertilizer application increased maize grain yield by 140 and 252% in 2013 and 2014, respectively. The greater grain yields of both maize and soybean with fertilizer application compared with no fertilizer input are consistent with previous results [8,10,14,19]. Indeed, poor kernel formation, increased abortion and ultimately lower grain yield under N stress have been reported widely [10,19].…”
Section: Discussionsupporting
confidence: 80%
“…This therefore calls for identification of complementary options to rehabilitate these degraded soils. In West Africa, mineral fertilizer has been found to increase crop yields substantially [8,13,14]. However, fertilizers are costly and even not available in most cases.…”
Section: Open Accessmentioning
confidence: 99%
“…This made the application of 90kg N ha -1 a better rate for this study. This finding is in agreement with that of Buah et al [18] which contrasted the 120 kg N ha -1 presently known to give the highest grain yield of maize in the northern Guinea Savanna [19]. The increased yield with N application is supported by the findings of others who reported increases in grain yield of maize [7,[13][14][15][16][17]20].…”
Section: Response To Nitrogensupporting
confidence: 89%